2023
DOI: 10.1007/s40291-022-00638-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of IDH Mutation Status in Formalin-Fixed Paraffin-Embedded Tissue in Gliomas

Abstract: Background and Objective Determination of isocitrate dehydrogenase (IDH) 1/2 mutational status is crucial for a glioma diagnosis. It is common for IDH mutational status to be determined via a two-step algorithm that utilizes immunohistochemistry studies for IDH1 R132H, the most frequent variant, followed by next-generation sequencing studies for immunohistochemistry-negative or immunohistochemistry-equivocal cases. The objective of this study was to evaluate adding a rapid real-time polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Other assay possibilities have been explored previously. For example, recent studies demonstrated the clinical utility of quantitative PCR and digital droplet PCR tests for determining IDH1/ IDH2 mutational status that had good concordance with IHC and NGS [ 9 , 10 ]. Digital droplet PCR (ddPCR) is a technique where a water-oil emulsion partitions the sample into many individual reactions so that either zero, one, or more target molecules are present in each independent reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Other assay possibilities have been explored previously. For example, recent studies demonstrated the clinical utility of quantitative PCR and digital droplet PCR tests for determining IDH1/ IDH2 mutational status that had good concordance with IHC and NGS [ 9 , 10 ]. Digital droplet PCR (ddPCR) is a technique where a water-oil emulsion partitions the sample into many individual reactions so that either zero, one, or more target molecules are present in each independent reaction.…”
Section: Discussionmentioning
confidence: 99%